2020
DOI: 10.3390/antiox9060531
|View full text |Cite
|
Sign up to set email alerts
|

Isosamidin from Peucedanum japonicum Roots Prevents Methylglyoxal-Induced Glucotoxicity in Human Umbilical Vein Endothelial Cells via Suppression of ROS-Mediated Bax/Bcl-2

Abstract: Methylglyoxal (MGO) is a highly reactive metabolite of glucose. Elevated levels of MGO induce the generation of reactive oxygen species (ROS) and cause cell death in endothelial cells. Vascular endothelial cell damage by ROS has been implicated in the progression of diabetic vascular complications, cardiovascular diseases, and atherosclerosis. In this study, the protective effect of isosamidin, isolated from Peucedanum japonicum roots, on MGO-induced apoptosis was investigated using human umbilical vein endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…MGO is a highly reactive dicarbonyl metabolite of glucose known to induce cellular apoptosis, oxidative stress, inflammation, and AGE formation in ECs [40,41]. The accumulation of MGO has been associated with organ dysfunction contributing to the pathogenesis of diabetes and vascular complications [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…MGO is a highly reactive dicarbonyl metabolite of glucose known to induce cellular apoptosis, oxidative stress, inflammation, and AGE formation in ECs [40,41]. The accumulation of MGO has been associated with organ dysfunction contributing to the pathogenesis of diabetes and vascular complications [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, MGO exposed HUVECs showed increased ROS production and apoptosis accompanied by an increase in Bax protein expression and a decrease in Bcl-2, increased phosphorylation of the MAPKS (p38, JNK, ERK), and decreased NF-κB activation [240,241]. In addition, Glyoxalase-1 (GLO-1) protein levels decreased while Nrf-2 remained unchanged (isosamidin counteracted all the effects) [241]. HUVECs incubated with MGO showed a significant increase in ROS production, monolayer permeability, actin stress fibers, and a decrease in gene and protein expression of ZO-1, Cx43, and the gap junctional intercellular communication (GJIC) [237].…”
mentioning
confidence: 95%
“…In both cases, MGO modified BSA induced the most significant decrease in GSH activity and increase in GPx activity compared to the other glycated proteins, whereas, in the presence of N-acetyl-cysteine (NAC) and aminoguanidine, the effects were reversed [167]. In another study, MGO exposed HUVECs showed increased ROS production and apoptosis accompanied by an increase in Bax protein expression and a decrease in Bcl-2, increased phosphorylation of the MAPKS (p38, JNK, ERK), and decreased NF-κB activation [240,241]. In addition, Glyoxalase-1 (GLO-1) protein levels decreased while Nrf-2 remained unchanged (isosamidin counteracted all the effects) [241].…”
mentioning
confidence: 99%
“…MGO- and MGO-mediated AGEs are increased in DN patients, and they are important factors in DN progression [ 58 60 ]. It is well established that MGO increases oxidative stress and cell damage/death in endothelial cells [ 61 ] and several kidney cells including mesangial cells [ 62 , 63 ], podocytes [ 64 ], and tubular epithelial cells [ 26 , 27 , 65 ]. According to several studies [ 26 28 , 35 ], including the present study, MGO-induced oxidative stress activates MAPK/NF κ B signaling and induces an inflammatory response in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%